Fulfilling Buy Online Pickup In-store Orders: the case of the retailers in the UK - DANG, QUYNH HOA (2018)
The surge of omni channel has become an irreversible trend that threats traditional brick-and-mortar retailers and brought about new opportunities to many players in the industries. Among them, Buy Online Pickup In-Store (BOPS) (alias “Click and Collect”) has gained greater influence on customers’ behaviours, but not been thoroughly understood, especially from the providers’ perspectives. This study investigates the case of the UK, a leading market for omni-channel retailing and provides an Arena simulation model coupled with an OptQuest optimization to gain insights into three different BOPS fulfilment policies that are differentiated by the fulfilment location (from the distribution centres, stores or both). The results suggest that the cost to fulfil each order range between £1.3 to £1.5 given the constraint of maximum 5% delaying rate of BOPS order fulfilment. Decentralised fulfilment seems to be more cost effective and less time-consuming than delivering from centralised distribution centre. The findings are useful for the design of effective distribution network to gain advantages from the surge of omni-channel retailing.